Australian Early Childhood Teachers' Understanding of Bullying. Issue 15 (August 2022) - Ey, Lesley-anne; Campbell, Marilyn
School bullying is a global phenomenon with teachers often at the forefront of responding to this behavior. It is, therefore, important that teachers are able both to understand and articulate what bullying is and to recognize bullying behavior. Ninety-five Australian early childhood teachers participated in an online survey to define bullying, fighting and identify the differences between the two behaviors. They were also asked to identify from 20 scenarios whether the behaviors depicted traditional bullying behaviors, cyberbullying behaviors, non-bullying face-to-face behaviors or non-cyberbullying behaviors. Results found that teachers described some of the three characteristics of bullying, that is, the intention to harm, power difference, and repetition; however, many teachers had difficulty clearly explaining the distinguishing differences between bullying and fighting. The majority of teachers identified the bullying behaviors in the scenarios; however, some teachers misinterpreted some non-bullying behaviors as bullying. The need to increase teacher's knowledge of bullying to support the prevention and intervention of bullying are discussed.